Application of turmeric as heat stress therapy for broiler chickens - Candra, Agung Adi; Putri, Dwi Desmiyeni; Oktyana, Sakhira Najla (International Journal of Advances in Applied Sciences, 2025)
This study aims to analyze the productivity of broilers kept in heat-stress conditions by drinking water mixed with turmeric (Curcuma domestica). This research was conducted in the Politeknik Negeri Lampung, Indonesia cage in September 2023. This study uses the experimental method by comparing the turmeric treatment group with as much as 500 mg/kg of chicken body weight which will be compared with the group without treatment (control). The results of the research on the provision of drinking water given turmeric (Curcuma domestica) to broilers kept under heat stress, based on the results of the study it can be concluded that the provision of drinking water mixed with turmeric (Curcuma domestica) as much as 500 mg/kg body weight of chickens on the productivity of broilers reared under heat stress conditions able to increases consumption and weight gain in chickens and can reduce feed conversion in broiler chickens experiencing heat stress.